The thermohydrodynamical picture of a charged Brownian particle - Barreiro, L. A. [UNESP]; Campanha, J. R. [UNESP]; Lagos, R. E. [UNESP] (My University, 2002)
We study a charged Brownian gas with a non uniform bath temperature, and present a thermohydrodynamical picture. Expansion on the collision time probes the validity of the local equilibrium approach and the relevant thermodynamical variables. For the linear regime we present several applications (some novel).
Keywords: Brownian motion; Thermodynamics